Jonas Kimštas-Žalgiris – personality and biographical traits - Pocius, Mindaugas (Genocidas ir rezistencija, 2020)
The article, based on the documentary materials kept in the Lithuanian Special Archives and the Lithuanian Central State Archive, the recollections and testimonies of the resistance participants and the relatives of Jonas Kimštas (Jonas Kimštas-Žalgiris), attempts to reveal the traits of Kimštas’s biography and his personality as well as his role in the history of the resistance movement. During the preparation of the article, a critical analysis of historical sources was performed, and a biographical method was used. Kimštas-Žalgiris was one of the most prominent, controversial and tragic leaders of the anti-Soviet resistance. In the history of the partisan war (1944–1953), he played a mixed and ambiguous role. His greatest merits fall for the unification of Aukštaitija partisans, the creation of Vytautas district and the Eastern Lithuanian region, and the organizational functioning of the headquarters of these partisan structures until August of 1952. He can also be accredited for the contribution to the centralization of the entire Lithuanian underground movement, and the development and operation of the Union of Lithuanian Freedom Fighters. Kimštas’s strong national identity was formed in the Polish-occupied Vilnius. This circumstance could have led to his hostility towards the Poles. In September-December of 1941, he worked as the Head of the 1st District of Vilnius of the Lithuanian Security Police Division. This fact can be considered as a collaboration with the Nazis and the occupying power of fascist Nazi Germany, however, no facts about the specific activities on this position, victims, or the participation in the Holocaust have been established so far. Kimštas valued family values. He was a family man who loved his wife and children and tried to support them materially, to protect them from danger, however, his living conditions were very unfavourable for that. Kimštas was a sincere, courageous, friendly, communicative, disciplined, careful, clear-thinking, and rational-minded, and had a developed intuition. He was a commander respected by his comrades. Freedom fighters and even the MGB agent J. Markulis considered him to be strong-willed, self-reliant, devoted to the struggle for independence, romantically in love with Lithuania and ready to die for it as an idealist. However, the nakedness of Kimštas’s personality began, and a certain “moment of truth” was revealed after the arrest, when a dramatic turn of consciousness occurred. On the first day (or days) of his arrest, Kimštas was probably tortured (by electricity and by tightening an iron ring on his head) and was applied huge psychological pressure until the partisan commander broke down. It is difficult to understand how, but suddenly the previous values, ideals, beliefs lost their meaning and importance, patriotism and idealism disappeared. The instinct of survival and the desire to live manifested themselves in full force. Kimštas began to actively cooperate with the MGB in destroying the last commanders, headquarters, and ordinary partisans of Eastern Lithuania. V. Paknienė’s version that the security guards injured Kimštas’s hands by torturing him in order to break him must be evaluated critically, as other independent sources contradict this statement. Their analysis supports the claim that Kimštas injured his hands and feet in March of 1953 during an attempt to commit suicide. According to the security guards, Kimštas wanted to end his life under the belief that he would be arrested and possibly shot after the exploitation by the agency. However, it is impossible to determine whether this was the real and only motive for the suicide, and this will remain a mystery. After the resistance movement had come to an end, Kimštas lived in poverty for the rest of his life, faced health problems and a bad mood, and perhaps moral suffering and suicidal thoughts as well.